2020
DOI: 10.1002/ldr.3827
|View full text |Cite
|
Sign up to set email alerts
|

The important role of soil moisture in controlling autumn phenology of herbaceous plants in the Inner Mongolian steppe

Abstract: Autumn phenology variation in temperate grassland is a direct indicator of land degradation, and a phenology‐based model has been used to simulate human‐induced land degradation. It is important to reveal how environmental factors influence autumn phenology of herbaceous plants. In this study, we examined the effects of temperature, photoperiod, and soil moisture on the leaf withering date (LWD) of four herbaceous species (Xanthium sibiricum, Plantago asiatica, Iris lactea, and Taraxacum mongolicum) at 15 site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 65 publications
2
5
0
Order By: Relevance
“…Furthermore, the sensitivity of vegetation to soil moisture has substantially increased since 1982 (Li, Migliavacca, et al, 2022). Previous studies found that not only temperature, but also plant-available water affect autumn phenological processes (Fu et al, 2022;Luo et al, 2021;Tao et al, 2021;Wu et al, 2022). For instance, Tao et al (2021) found that soil moisture considerably constrained the autumn phenology of herbaceous plants, which means that the accuracy of the CDD model could be improved using soil moisture based on in situ data.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the sensitivity of vegetation to soil moisture has substantially increased since 1982 (Li, Migliavacca, et al, 2022). Previous studies found that not only temperature, but also plant-available water affect autumn phenological processes (Fu et al, 2022;Luo et al, 2021;Tao et al, 2021;Wu et al, 2022). For instance, Tao et al (2021) found that soil moisture considerably constrained the autumn phenology of herbaceous plants, which means that the accuracy of the CDD model could be improved using soil moisture based on in situ data.…”
mentioning
confidence: 99%
“…Previous studies found that not only temperature, but also plant-available water affect autumn phenological processes (Fu et al, 2022;Luo et al, 2021;Tao et al, 2021;Wu et al, 2022). For instance, Tao et al (2021) found that soil moisture considerably constrained the autumn phenology of herbaceous plants, which means that the accuracy of the CDD model could be improved using soil moisture based on in situ data. However, a generalized autumn phenology that takes into account soil moisture, and which can be applied at large scales, is still lacking.…”
mentioning
confidence: 99%
“…Several studies have demonstrated its better performance in modeling leaf coloration and fall for many woody species compared to the CDD model (Archetti et al, 2013; Delpierre et al, 2009; Keenan & Richardson, 2015); furthermore, according to the significant influence of spring phenology on autumn phenology of some woody species, Keenan and Richardson (2015) further modified it by considering the effect of the beginning of the growing season on autumn phenology, which also slightly improved the accuracy of autumn phenology simulation in Harvard Forest. But the limited influence of leaf unfolding date on leaf senescence was found for herbaceous plants in China (Ren, Vitasse, et al, 2022; Tao et al, 2021). Meanwhile, Lang et al (2019) developed another model by using the interaction of photoperiod and minimum temperature to nonlinearly determine the daily leaf senescence rate of plants, which also exhibited an improved accuracy of leaf senescence compared with previous models for both woody and herbaceous species.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, Lang et al (2019) developed another model by using the interaction of photoperiod and minimum temperature to nonlinearly determine the daily leaf senescence rate of plants, which also exhibited an improved accuracy of leaf senescence compared with previous models for both woody and herbaceous species. Additionally, the incorporation of water factors can also ameliorate the simulation performance of autumn phenology of herbaceous species compared with temperature‐based models only (Lang et al, 2019; Ren et al, 2019; Tao et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation